2014
DOI: 10.1155/2014/325048
|View full text |Cite
|
Sign up to set email alerts
|

Not Always Asthma: Clinical and Legal Consequences of Delayed Diagnosis of Laryngotracheal Stenosis

Abstract: Laryngotracheal stenosis (LTS) is a rare condition that occurs most commonly as a result of instrumentation of the airway but may also occur as a result of inflammatory conditions or idiopathically. Here, we present the case of a patient who developed LTS as a complication of granulomatosis with polyangiitis (GPA), which was misdiagnosed as asthma for 6 years. After an admission with respiratory symptoms that worsened to the extent that she required intubation, a previously well 14-year-old girl was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 16 publications
0
23
0
4
Order By: Relevance
“…The literature review and our practical experiences showed that most patients with PITS were misdiagnosed and treated for asthma for a long time (26) before finally undergoing an emergency tracheostomy to secure their airways, which actually makes the scenario worse because the treatment involves the resection and reconstruction of the trachea. Therefore, the follow-up of ICU patients with a history of endotracheal intubation is very important for diagnosing PITS, which can lead to severe complications or even death.…”
Section: Discussionmentioning
confidence: 99%
“…The literature review and our practical experiences showed that most patients with PITS were misdiagnosed and treated for asthma for a long time (26) before finally undergoing an emergency tracheostomy to secure their airways, which actually makes the scenario worse because the treatment involves the resection and reconstruction of the trachea. Therefore, the follow-up of ICU patients with a history of endotracheal intubation is very important for diagnosing PITS, which can lead to severe complications or even death.…”
Section: Discussionmentioning
confidence: 99%
“…La obstrucción de la vía aérea se puede presentar con ruidos respiratorios clínicamente difíciles de distinguir de las sibilancias. 13 La dificultad en el diagnóstico aumenta en situaciones en las que la obstrucción de la vía aérea se produce de forma insidiosa.…”
Section: Discussionunclassified
“…11 La ES es una causa poco frecuente de una presentación clínica muy común (disnea de esfuerzo, ruidos respiratorios y reducción de flujo espiratorio máximo). 12 La dificultad en el diagnóstico aumenta en situaciones en las que la estenosis se produce de forma insidiosa, como en la GW. El retraso y el error diagnóstico ocurren con frecuencia, lo que puede evitarse en gran medida mediante un índice apropiado de sospecha clínica y un examen de la función pulmonar, sobre todo, si el paciente no responde a la terapia inicial de asma.…”
Section: 8unclassified
“…El retraso y el error diagnóstico ocurren con frecuencia, lo que puede evitarse en gran medida mediante un índice apropiado de sospecha clínica y un examen de la función pulmonar, sobre todo, si el paciente no responde a la terapia inicial de asma. 12 Las pruebas de función pulmonar son anormales en el 60% de los pacientes con ES, y se observa en la curva flujo/volumen un aplanamiento de la curva en inspiración y en espiración que conforma la curva cajón característica, presente en nuestra paciente.…”
Section: 8unclassified